Social-Ecological Analysis of the Factors Influencing Shanghai Adolescents’ Table Tennis Skills: A Cross-Sectional Study - Xiao, Yi; Huang, Wenwen; Lu, Miaomiao; Ren, Xiaoling; Zhang, Pei (Frontiers in Psychology, 2020)
The main purpose of this study is to explore the factors that affect adolescents’ table tennis skills (ATTS) among adolescents in Shanghai from the social ecological perspective, including individual factors, social support, and physical environment. This study included 1,526 students (47.6% (n=726) were female, 52.4% (n=800) were male) whose ages ranged from 9 to 16 years old from Shanghai primary and secondary schools (M = 12.31, SD = 1.32). Participants completed a questionnaire based on the social ecological theory after taking the ATTS test. Structural equation model was applied to test the hypothesized relationships between the study variables. The relationship model incorporating individual factors, social support, physical environment and ATTS test score was assumed to be in agreement with the data [x2= 1415.754, x2/df = 4.96, p < 0.001; CFI = 0.914; IFI = 0.930; NFI = 0.921; RMSEA = 0.032]. The investigation results showed that social support and physical environment can promote adolescents’ scores on the ATTS test. Among the levels of social ecology, individual factors were the most important factors in the improvement of ATTS. The level with the most significant impact on ATTS is that of individual factors, followed by social support and, finally, the physical environment. Specifically, at the level of individual factors, motivation was more effective than self-efficacy; at the level of social support, the order of different factors’ impact from high to low is friends’ support, parents’ support and PE teachers’ support; at the level of physical environment, the school environment is more important than the community environment.